(Re)Centering Quality in Early Childhood Education: Toward Intersectional Justice for Minoritized Children - Souto-Manning, Mariana; Rabadi-Raol, Ayesha (Review of research in education, 2018)
In this chapter, we offer a critical intersectional analysis of quality in early childhood education with the aim of moving away from a singular understanding of "best practice," thereby interrupting the inequities such a concept fosters. While acknowledging how injustices are intersectionally constructed, we specifically identified critical race theory as a counterstory White supremacy, culturally relevant and sustaining pedagogies as counterstories to monocultural teaching practices grounded in deficit and inferiority paradigms, and translanguaging as a counterstory to the (over)privileging of dominant American English monolingualism. While each of these counterstories forefronts one particular dimension of oppression, together they account for multiple, intersecting systems of oppressions; combined, they expand the cartography of early childhood education and serve to (re)center the definitio of quality on the lives, experiences, voices, and values of multiply minoritized young children, families, and communities. Rejecting oppressive and reductionist notions of quality, through the use of re-mediation, this article offers design principles for intersectionally just early childhood education with the potential to transform the architecture of quality.